Repeatability of bolus and continuous thermodilution for assessing coronary microvasculatory function. (3rd October 2022) - Gallinoro, E; Fernandez-Peregrina, E; Bertolone, D T; Paolisso, P; Bermpeis, K; Esposito, G; Belmonte, M; Candreva, A; Mileva, N; Munhoz, D; Sonck, J; Barbato, E; et al.
Abstract: Introduction: The bolus thermodilution-derived index of microcirculatory resistance (IMR) has emerged over years as the standard of reference to invasively define coronary microvascular dysfunction (CMD). However, the technique still presents some limitations, mainly related to the fact that manual injection of saline bolus accounts for some variance in the measurements. Continuous intracoronary thermodilution has been recently introduced as a tool to directly quantify absolute coronary flow and microvascular resistance both at rest and during hyperemia and has shown to be safe and operator independent. Microvascular resistance reserve (MRR), derived from continuous thermodilution, has been validated as novel index specific for microcirculation and independent from myocardial mass. Purpose: To compare head-to-head the intra-observer repeatability of bolus and continuous thermodilution for assessing microvascular function. Methods: Patients undergoing coronary angiography in the absence of obstructive coronary artery disease were prospectively enrolled. Bolus and continuous intracoronary thermodilution measurements were performed in duplicates in the left anterior descending artery (LAD). Patients were randomly assigned in a 1:1 ratio to undergo first bolus thermodilution or first continuous thermodilution assessment. Results: A total of 102 patients were enrolled. Average FFR was 0.86±0.06. Coronary Flow Reserve (CFR) calculated with continuous thermodilution (CFRthermo) was significantly lower than bolus thermodilution-derived CFR (CFRbolus) (2.63±0.65 and 3.29±1.17, respectively, p<0.001). CFRthermo showed a lower variability and a higher agreement than CFRbolus (variability 12.74±10.41% vs 31.26±24.85%, respectively, p<0.001; ICC= 0.78 (0.70–0.85) and 0.48 (0.32–0.62), respectively, p<0.001, Figure 1). Both MRR and IMR showed a good agreement (ICC 0.81 (0.74–0.87) and 0.80 (0.71–0.86)) but the variability of the MRR was significantly lower (12.44±10.06% vs 24.24±19.27, respectively, p<0.001, Figure 1). Reproducibility data of all indices derived from duplicated measurements of bolus and continuous thermodilution are reported in Table 2. Conclusion: Continuous intracoronary thermodilution has a higher repeatability than bolus thermodilution in the assessment of CMD. Funding Acknowledgement: Type of funding sources: None.